The seaside resorts in the "Summer Issues" of the illustrated magazine Elegancias (a transatlantic view) - Avilés, Clara María (Meridional. Revista Chilena de Estudios Latinoamericanos, 2024)
The aim of this paper is to explore how the magazine Elegancias (1911-1914), published in Paris under the literary direction of Rubén Darío, addressed the practice of coastal vacationing and disseminated seasonal imaginaries at the turn of the century. Focusing on two special issues dedicated to summer vacations, the research highlights the magazine's engagement with the trends and concerns of the time, such as literature, art, fashion, and travel during the summer season. Through this analysis, it is demonstrated that Elegancias sought to insert itself into the discursive representation of the summer season by the sea during the early decades of the 20th century, thus shaping the perceptions of its readers. Ultimately, this research sheds light on the cultural and historical importance of Elegancias as a transatlantic communication medium with roots in the French capital but with its own identity in the Spanish-speaking world.